Nanotechnology and development : what's in it for emerging countries? - Ramani, Shyama V., 1960- (Cambridge University Press, 2014)
"Examines the nature and magnitude of the nanotechnology divide between high income countries and the rest of the world"--Resumé vydavatele
Keywords: nanotechnologie -- rozvojové země; technologický rozvoj -- rozvojové země; ekonomický růst -- rozvojové země; nanotechnology -- developing countries; technological development -- developing countries; economic development -- developing countries; rozvojové země -- hospodářské poměry; developing countries -- economic conditions; kolektivní monografie; collective monographs